Analysis of The Contribution of Motor Vehicle Taxes and Transfer Fees For Motorized Vehicles on Regional Income of Gorontalo City - Bumulo, Frahmawati; Dai, Sri Indriyani S.; Dukey, Zainaldi (Proceedings of International Conference of Graduate School on Sustainability, 2025)
This study uses secondary data, which includes data published by the City Samsat and the Regional Finance Agency, as well as institutions related to the title of this research. The data used in this study is time series data for the years 2013-2020, which includes the effectiveness and contribution of motor vehicle taxes and transfer fees for motorized vehicles in the Gorontalo City area. The results showed that the analysis of the effectiveness of the motor vehicle tax on the City of Gorontalo’s Regional Original Income during 2013 to 2020 was 97.82%, the analysis of the effectiveness of the transfer of motorized vehicle title fees on the Regional Original Income of the City of Gorontalo during 2013 to 2020 was 90.66%. From this value, it can be said that the effectiveness of the motor vehicle tax and transfer fees for motorized vehicles on the Gorontalo City Original Revenue from 2013 to 2020 is effective. The analysis of the contribution of motorized vehicle taxes to Gorontalo City’s Original Regional Revenue during 2013-2020 is 23.52%, and the analysis of the contribution of motorized vehicle title transfer fees to Gorontalo City’s Regional Original Income during 2013-2020 is 29.84%.